Incidence of Larvae Deformities in Chironomus Species (Diptera: Chironomidae) as Bio-Indicators of Water Quality in Lake Victoria Basin, Kenya - Nyakeya , Kobingi; Nyamora , Jane; Kerich, Emmy Cheptoo (African Journal of Education,Science and Technology (AJEST), 2018)
Lake Victoria is the second largest freshwater body in the world and one of the richest ecosystems in terms of biodiversity but is facing a major environmental concern originating from pollution, degradation and overfishing. This study sought to determine the incidence of larvae deformities in Chironomus species (Diptera: Chironomidae) as bio-indicators of water quality in Lake Victoria Basin, Kenya. Chironomids were sampled upstream and downstream of Rivers Nzoia and Mbogo for tests in the laboratory. They were exposed to dilutions of kraft paper-mill and sugar cane factory effluents for 21 days under controlled conditions. Results for the deformity effluent toxicity tests were presented as means (±Standard Error of Mean, SEM). Data for the tests expressed as the proportion deformity was first transformed by the Probit analysis to check for normality before analysis. Two way ANOVA for the deformity tests was run with the station and concentration as the main factors with the station x concentration interaction effect and where there was no interaction then 1-way ANOVA was run with the main individual factors only (i.e. effluent, station and concentration). Post hoc Tukey test was then performed to identify means of concentrations for deformities of the Chironomus midges differing from one another. All pair wise multiple comparisons of stations and effluent concentrations was done to determine whether there existed any effect. One-Way ANOVA was also, used to determine significant difference between the control and the effluent concentrations. All analysis was done in Sigma Plot and the significant differences were inferred at α=0.05 level. There were significant effects (p<0.05) between effluents on abnormality of Chironomus species. The study concluded that Chironomus species are sensitive to sugar cane processing and paper mill effluents, hence can be used as test organism in monitoring the health of riverine ecosystems in LVB for management purposes